Education - Hanley-Maxwell, Cheryl; Collet-Klingenberg, Lana. (Thousand Oaks, Calif. : SAGE Publications, 2011)
'This volume in The SAGE Reference Series on Disability explores education issues for people with disabilities and is one of eight volumes in the cross-disciplinary and issues-based series, which examines topics central to the lives of individuals with disabilities and their families. With a balance of history, theory, research, and application, specialists set out the findings and implications of research and practice for others whose current or future work involves the care and/or study of those with disabilities, as well as for the disabled themselves. The concise, engaging presentational style emphasizes accessibility. Taken individually, each volume sets out the fundamentals of the topic it addresses, accompanied by compiled data and statistics, recommended further readings, a guide to organizations and associations, and other annotated resources, thus providing the ideal introductory platform and gateway for further study. Taken together, the series represents both a survey of major disability issues and a guide to new directions and trends and contemporary resources in the field as a whole'--Provided by publisher.
Introduction, background, and history / Lana Collet-Klingenberg and Cheryl Hanley-Maxwell -- Current issues, controversies, and solutions / Cheryl Hanley-Maxwell and Lana Collet-Klingenberg -- Chronology of critical events / Mary-Elizabeth Glass, Chen-chen Cheng, Cheryl Hanley-Maxwell, and Lana Collet-Klingenberg -- Biographies of key contributors in the field / Cheryl Hanley-Maxwell and Lana Collet-Klingenberg -- Annotated data, statistics, tables, and graphs / Amy C. Stevens Griffith and Cheryl Hanley-Maxwell -- Annotated list of organizations and associations / Michelle Raasch, Minyoung Kim, Lana Collet-Klingenberg, and Cheryl Hanley-Maxwell -- Selected print and electronic resources / Sharon M. Kolb and Lana Collet-Klingenberg -- Glossary of key terms.
Includes bibliographical references and index.
Keywords: Special education -- United States -- History; Children with disabilities -- Education -- United States -- History; Children with social disabilities -- Education -- History; Educational equalization -- United States -- History